Data Analysis: Finding the Most Effective Factors Causing Cancer Deaths - Babu, V. Naveen; Murali, T; Hussian, Sk Meer; S. Nava Chaitanya,; Varalakshmi, Madda (International Journal of Computer Sciences and Engineering, 2025)
The spreading of abnormal cells in the human body with much potential is a basic cause of disease cancer. The growth of abnormal cells may be affected by age group, being disease-oriented, or type of location in which people live and many factors. Because of the circumstances, there is no possibility of avoiding the growth of abnormal cells, but by taking corrective measures the growth can be slowed down to some extent. In addition to that, it will envisage the cancer causes which in turn can be used to create awareness among the people. In this fact, it is important to determine if someone has a high cancer risk by using biological test results which have been recorded. By working on these sample data, we can focus on finding the most influential factors that affect cancer. In this research, by applying a suitable Machine Learning algorithm on the data which have been collected using surveys, we are able to find the most important factors and mainly classification type of Machine Learning algorithms to be used for performance analysis.